Narrative review of cytoreductive surgery and intraperitoneal chemotherapy for peritoneal metastases in ovarian cancer - Boerner, Thomas (J Gastrointest Oncol, 2021)
Due to numerous factors, such as no specific symptoms and ineffective screening to identify premalignant or early-stage disease, most patients with ovarian cancer present with advanced-stage disease and overt peritoneal metastases. Currently, the most effective treatment for these patients is complete cytoreductive surgery with systemic platinum/taxane-based chemotherapy. Over the past few decades, many researchers have evaluated the use of postoperative normothermic intraperitoneal (NIPEC) and intraoperative hyperthermic intraperitoneal chemotherapy (HIPEC) delivery as additional treatment modalities. Here, we will review the current status and future directions for these treatment strategies in the management of ovarian cancer. Most of the studies in this area of research have been retrospective in nature, limited by heterogeneous patient populations and large variance in chemotherapeutic regimens used, leading to mixed results and difficulties in evaluating the clinical impact of the data. More mature data from prospective trials are lacking, and IP therapy for advanced ovarian cancer should still be considered an investigational approach and evaluated only in clinical trials; the exception is for patients with stage III disease who undergo interval debulking surgery after neoadjuvant chemotherapy, for whom HIPEC can be considered in selected patients as part of first-line therapy.